Push-out force and impulse measurement of seven types of small arms ammunition with three different surface states - Muster, Michael; Hameed, Amer; Wood, David C.; Wasmer, Kilian (American Institute of Physics (AIP), 2019)
This study analyzes the influence of lubrication treatments on the force absorbed by the breech bolt called push-out force. The results are of high interest for weapon-safety and durability studies, especially when it comes to weapon maintenance. A barrel-ammunition combination represents an expanding vessel under high pressure. The pressure rises from ambient up to 420 MPa in less than a millisecond. During such a highly dynamic process, purely static equations, describing the problem of the casing push-out force, may not be applied. Besides the dynamic behavior, the surface properties and geometry also play an important role. To investigate the push-out force, a measurement system based on a force washer was built. This system was validated using a crusher method and finite element analysis. The impulse was calculated using the data of the measured force to obtain additional information about the force-time properties of the push-out behavior. Untreated ammunition and two lubrication systems: “ice layer” and “oil lubricated,” as well as seven different ammunition sizes ranging from 5.56 to 12.7 mm were considered. The response was the force absorbed by the bolt while the cartridge provides rear obturation to the combustion gases. It was found that both the casing geometry and its treatments have a significant influence on the push-out force.